Half-day Consultancy and Training on Research Methodology - Mohd Rashid, Ab Hamid (2023)
UMP Paya Besar, 26 Feb 2023 - Centre for Mathematical Sciences in collaboration with Mutiara Biru Ehsan(MBE) has succesfully organised half-day consultancy and training on Research Methodology which was delivered by Professor Ts. Dr. Mohd Rashid bin Ab Hamid, an HRD Corp Certified Trainer (12030).